Oxidative balance score and mortality: mediating role of insulin resistance across age strata in the NHANES cohort - Zhang, Lin; Zhang, Heming; Xiang, Hongxia; Zhang, Jiachen; Gong, Wei; Xv, Junjie; Yu, Xue (Frontiers in Nutrition, 2025)
BackgroundThis study examined the association between oxidative balance score (OBS), a composite measure of oxidative/antioxidative factors, and mortality, while investigating insulin resistance (IR) indices as potential mediators using a nationally representative cohort.MethodsA cohort of 11,849 U. S. adults from NHANES (2007–2018) was analyzed. OBS integrated 16 dietary and 4 lifestyle components. Mortality risks (all-cause, cardiovascular, cancer) were assessed via weighted Cox models. Mediation analysis evaluated the indirect effects of five IR indices (TyG index, TG/HDL-C, HOMA-IR, eGDR, VAI) on OBS-mortality associations, with statistical validation of mediation effects. Analyses were stratified by age (<65 vs. ≥65 years) and adjusted for sociodemographic, behavioral, and clinical covariates.ResultsHigher OBS reduced risks of all-cause (HR = 0.652, 95% CI: 0.525–0.81) and cardiovascular mortality (HR = 0.605, 95% CI: 0.408–0.898), but not cancer mortality. Innovatively, eGDR mediated 17% of OBS’s protective effect on all-cause mortality in adults <65 years, while TyG index and HOMA-IR showed weaker mediation. No IR mediation occurred in older adults (≥65 years).ConclusionHigher OBS levels were inversely associated with all-cause and cardiovascular mortality, partially mediated by insulin resistance pathways. These findings highlight OBS as a potential prognostic indicator for mortality risk.